We are Just People: Transgender Individuals' Experiences of a Local Equal Rights Debate. Issue Volume 13:Issues 3(2019) (3rd July 2019) - Robertson, Derek L.; Pow, Allison M.; Hunt, David; Hudson, Brittany; Mickelsen, Rachel
Abstract: This phenomenological inquiry investigated the experiences of 13 transgender individuals living in Houston, Texas, when an ordinance providing protections for transgender persons was passed and later repealed. The six themes garnered from the data were (a) from feeling ecstatic to devastated to fearful; (b) being dehumanized, labeled, and violated; (c) being abandoned and singled out for discrimination; (d) being depicted as threat in public restrooms; (e) having fears and hopes for equality; and (f) defending the humanity of transgender people. Implications for clinical practice, advocacy, and future studies are discussed.